Medical management of cerebral edema in large hemispheric infarcts - DeHoff, Grace; Lau, Winnie (Frontiers in Neurology, 2022)
Acute ischemic stroke confers a high burden of morbidity and mortality globally. Occlusion of large vessels of the anterior circulation, namely the intracranial carotid artery and middle cerebral artery, can result in large hemispheric stroke in ~8% of these patients. Edema from stroke can result in a cascade effect leading to local compression of capillary perfusion, increased stroke burden, elevated intracranial pressure, herniation and death. Mortality from large hemispheric stroke is generally high and surgical intervention may reduce mortality and improve good outcomes in select patients. For those patients who are not eligible candidates for surgical decompression either due timing, medical co-morbidities, or patient and family preferences, the mainstay of medical management for cerebral edema is hyperosmolar therapy. Other neuroprotectants for cerebral edema such as glibenclamide are under investigation. This review will discuss current guidelines and evidence for medical management of cerebral edema in large hemispheric stroke as well as discuss important neuromonitoring and critical care management targeted at reducing morbidity and mortality for these patients.